2020
DOI: 10.1093/hropen/hoaa054
|View full text |Cite
|
Sign up to set email alerts
|

Uterine bathing with sonography gel prior to IVF/ICSI-treatment in patients with endometriosis, a multicentre randomised controlled trial

Abstract: STUDY QUESTION What is the effect of uterine bathing with sonography gel prior to IVF/ICSI-treatment on live birth rates after fresh embryo transfer in patients with endometriosis? SUMMARY ANSWER After formal interim analysis and premature ending of the trial, no significant difference between uterine bathing using a pharmacologically neutral sonography gel compared to a sham procedure on live birth rate after fresh embryo transfer in endometriosis patients (26.7% vs. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…34 participants from hysteroscopy group and 58 participants from the control group underwent a second embryo transfer procedure using frozen embryos. From the 34 patients in the hysteroscopy group, 21 had positive pregnancy test (61.76%) and in the control group, from the 58 participants, 25 Similar to the first transfer, none of the outcome measures in the second transfer were significantly different between 2 groups. However, the live birth rate was 20% higher in the intervention group.…”
Section: Frozen Embryo Transfer Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…34 participants from hysteroscopy group and 58 participants from the control group underwent a second embryo transfer procedure using frozen embryos. From the 34 patients in the hysteroscopy group, 21 had positive pregnancy test (61.76%) and in the control group, from the 58 participants, 25 Similar to the first transfer, none of the outcome measures in the second transfer were significantly different between 2 groups. However, the live birth rate was 20% higher in the intervention group.…”
Section: Frozen Embryo Transfer Resultsmentioning
confidence: 92%
“…Some studies suggested the potential effect of immunomodulation triggered by uterine bathing using Lipiodol ® ( 23 , 24 ). In contrast, some other trials found no difference in using pharmacologically neutral gels for uterine bathing ( 25 , 26 )…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Lier M.C.I. performed an RCT in endometriosis patients in which gel was injected into the uterus before IVF/intracytoplasmic sperm injection (ICSI) treatment, and they did not find a favorable effect of uterine infusion [25], which suggests that the fertility-enhancing effects may be related to the properties of oil-based media. Lipiodol and ethiodized poppyseed oil are clinically available oil-based mediums, and Papaver somniferum seeds, the primary raw materials in oil-based media agents, contain natural opium [26].…”
Section: Discussionmentioning
confidence: 99%